2003
DOI: 10.1016/s0040-6090(03)00067-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis and microstructure of PVD monolayer TiN and multilayer TiN/(Ti,Al)N coatings

Abstract: Two PVD titanium nitride based coatings; monolayer TiN and multilayer resulting from the stacking of TiN and (Ti,Al)N layers were evaluated with respect to their stress state and microstructure. The TiN was deposited by triode evaporation ion plating, whereas the TiNy(Ti,Al)N was deposited using a reactive hybrid deposition process consisting of a combination of electron beam evaporation of Ti and DC magnetron sputtering of a Ti-Al alloy. The structural and mechanical state characterisations of the as-deposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 22 publications
3
52
0
6
Order By: Relevance
“…The monolayer TiAlCrN coating has a nano-crystalline structure [20] and the lowest Table 2 shows that the residual stress is highly compressive for all the coatings studied. This range of residual stress is normal for the multilayer PVD coatings deposited under conditions specified in the experimental section [22]. This is beneficial considering the heavy loaded conditions associated with the experiments performed and prevents excessive chipping of the cutting edge under operation.…”
Section: Structural Analysismentioning
confidence: 99%
“…The monolayer TiAlCrN coating has a nano-crystalline structure [20] and the lowest Table 2 shows that the residual stress is highly compressive for all the coatings studied. This range of residual stress is normal for the multilayer PVD coatings deposited under conditions specified in the experimental section [22]. This is beneficial considering the heavy loaded conditions associated with the experiments performed and prevents excessive chipping of the cutting edge under operation.…”
Section: Structural Analysismentioning
confidence: 99%
“…Coatings' stresses depend on the layer thickness, substrate materials, and deposition temperature. De Hosson 25,26 showed that the stress in TiN and AlTiN layers is related to the coating thickness, substrate roughness, and grain size. In our experiments, the deposition parameters of the Ti and AlTiN layer are the same for different samples, therefore the stress levels in the AlTiN layer are the same.…”
Section: Resultsmentioning
confidence: 99%
“…The core is identical as in the case of the type 1 system. The physical and mathematical model that makes it possible to determine the internal thermal stresses was developed based on the [18][19][20][21][22][23][24] and classical theory of elastic-plastic materials [25]. The details of the design of the computer model used based on an FEM analysis are contained in the studies [13,26] and in the documentation of the Comsol package, with the aid of which the calculations were made.…”
Section: Computer Modelmentioning
confidence: 99%
“…For the purpose of computer designing and testing of the properties of coatings, simulation packages are used. They are based on the finite element method (FEM), and they make it possible to determine the state of internal stresses and strains in substrate/coating systems, which occur as a result of external thermomechanical loads [18][19][20][21][22][23][24][25]. This offers a possibility to conduct virtual in-service tests that support the selection of the optimal physico-chemical parameters and the geometry of anti-wear coatings [26][27][28].…”
Section: Introductionmentioning
confidence: 99%